Mechanisms of Kwashiorkor-Associated Immune Suppression: Insights From Human, Mouse, and Pig Studies - Michael, Husheem; Amimo, Joshua O.; Rajashekara, Gireesh; Saif, Linda J.; Vlasova, Anastasia N. (Frontiers in Immunology, 2022)
Malnutrition refers to inadequate energy and/or nutrient intake. Malnutrition exhibits a bi-directional relationship with infections whereby malnutrition increases risk of infections that further aggravates malnutrition. Severe malnutrition (SM) is the main cause of secondary immune deficiency and mortality among children in developing countries. SM can manifest as marasmus (non-edematous), observed most often (68.6% of all malnutrition cases), kwashiorkor (edematous) is detected in 23.8% of cases, and marasmic-kwashiorkor is identified in 7.6% of SM cases. Marasmus and kwashiorkor occur due to calorie-energy and protein-calorie deficiency (PCD), respectively. Kwashiorkor and marasmic-kwashiorkor present with reduced protein levels, protein catabolism rates and altered levels of micronutrients leading to uncontrolled oxidative stress, exhaustion of anaerobic commensals, and proliferation of pathobionts. Due to these alterations, kwashiorkor children present with profoundly impaired immune function, compromised intestinal barrier and secondary micronutrient deficiencies. Kwashiorkor-induced alterations contribute to growth stunting and reduced efficacy of oral vaccines. SM is treated with antibiotics and ready-to-use therapeutic foods with variable efficacy. Kwashiorkor has been extensively investigated in gnotobiotic (Gn) mice and piglet models to understand its profound immediate and long-term effects on children health. Due to numerous physiological, and immunological similarities between pigs and humans, pig represents a highly relevant model to study kwashiorkor pathophysiology and immunology. Here we summarize the impact of kwashiorkor on children’s health and review the relevant findings from human and animal studies. We also discuss the reciprocal interactions between PCD and rotavirus - a highly prevalent enteric childhood pathogen which pathogenesis and immunity are affected by childhood SM.